Architektura a umění - Ondruch, Matěj (Vysoké učení technické v Brně. Fakulta architektury)
Cílem závěrečné práce je studie novostavby Městské galerie Litomyšl. V současné době funguje Městská galerie spíše improvizovaně v nevyhovujícím historickém objektu na náměstí. Tento dům nebyl postaven pro významnou kulturní instituci, jakou galerie bezesporu je, ale pro bydlení měšťanů. Kulturně a historicky bohaté město jako Litomyšl si ovšem zaslouží, aby Městská galerie sídlila v objektu, který byl pod tímto záměrem navržen a postaven.

The aim of this bachelor project is to design a new building for the Municipal Art Gallery in Litomyšl, Czech Republic. Currently, the institution seats in one of the narrow, old town houses at the historic Smetanovo square. The building was originally bulit for a different purpose and therefore provides with unsuitable exhibition conditions and lack of exhibition space. After a detailed analysis of the Litomyšl town and its urban structure, the work defined a suitable site for the art gallery in the historic town center. In the author´s opinion, the town such as Litomyšl does not need any monumental nor too pompous art gallery and therefore the proposed scheme is adapted to the scale of the surroundings with respect to its cultural importance. It provides with sufficient exhibition space and quality conditions for all kinds of art.
Architecture and Art
Keywords: ARCHITEKTURA; URBANISMUS; UMĚNÍ; LITOMYŠL; GALERIE; ARCHITECTURE; URBANISM; ART; LITOMYŠL; GALLERY